2005
DOI: 10.1111/j.1742-4658.2005.04594.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory properties of cystatin F and its localization in U937 promonocyte cells

Abstract: Human papain-like cathepsins were long believed to be responsible for terminal protein degradation in the lysosomes. This view changed dramatically when they were found to be involved in a number of important cellular processes, such as antigen presentation [7]. Their high proteolytic potential, which can be very harmful, requires the activity of papain-like cathepsins to be strictly regulated. Their endogenous protein inhibitors act as one of the main means of regulation [8]. The best characterized are the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
79
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 49 publications
(81 reference statements)
11
79
0
Order By: Relevance
“…Cystatin F has a unique cathepsin inhibition profile, with a clear preference for cathepsins F, K, L, and V (20,22). Interactions of cystatins with family C1 cysteine proteases are mediated by three regions, an N-terminal segment and the two hairpin loops L1 and L2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cystatin F has a unique cathepsin inhibition profile, with a clear preference for cathepsins F, K, L, and V (20,22). Interactions of cystatins with family C1 cysteine proteases are mediated by three regions, an N-terminal segment and the two hairpin loops L1 and L2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The inhibitor shares Ͻ35% sequence identity with other type II cystatins and possesses a unique extension of ϳ6 amino acids at its N terminus. Compared with other cystatins, the protein exhibits a distinct specificity profile, binding tightly to cathepsins F, K, L, and V, less tightly to cathepsins S and H, and not inhibiting cathepsins B, C, or X (20,22). Although cystatin F can inhibit AEP, its affinity is reduced compared with other AEP binding cystatins (11).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…We recently showed that cystatin F, which is principally found in immune cells, could inhibit cathepsin C [65]. Cystatin F is made initially as an inactive disulphide-linked dimer [66][67][68]. Reduction generates an inhibitor able to target some endopeptidases but we found that carbohydrate-driven lysosomal targeting [69] resulted in monomerisation and activation by proteolysis, which extended the protease target range to enzymes such as cathepsin C [65].…”
mentioning
confidence: 87%
“…It is expressed as a disulphide linked dimer and targeted to the endosomal/lysosomal pathway through the mannose-6-phosphate sorting machinery (76), where it can regulate the activity of cysteine peptidases. However, cystatin F is not active as an inhibitor of cysteine cathepsins until it is converted to the monomeric form (77). Dimer to monomer conversion is facilitated by proteolytic cleavage at the N-terminus (78), probably by cathepsin V (41).…”
Section: Cystatins and The Immune Responsementioning
confidence: 99%